2023
DOI: 10.1111/mec.16916
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the genetic basis of vertebrate dispersal combining RNA‐seq, RAD‐seq and quantitative genetics

Abstract: Although animal dispersal is known to play key roles in ecological and evolutionary processes such as colonization, population extinction and local adaptation, little is known about its genetic basis, particularly in vertebrates. Untapping the genetic basis of dispersal should deepen our understanding of how dispersal behaviour evolves, the molecular mechanisms that regulate it and link it to other phenotypic aspects in order to form the so‐called dispersal syndromes. Here, we comprehensively combined quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 141 publications
0
8
0
Order By: Relevance
“…A recent study on a semi‐natural population of common lizards showed that expression of circadian clock genes differed between dispersers and residents. However, ADORA2A or UPB1 were not among the dispersal‐related genes identified in this species (San‐Jose et al., 2023). Moreover, clock‐linked genes may also influence migratory timing in the American kestrel ( Falco sparverius ; Bossu et al., 2022).…”
Section: Discussionmentioning
confidence: 93%
“…A recent study on a semi‐natural population of common lizards showed that expression of circadian clock genes differed between dispersers and residents. However, ADORA2A or UPB1 were not among the dispersal‐related genes identified in this species (San‐Jose et al., 2023). Moreover, clock‐linked genes may also influence migratory timing in the American kestrel ( Falco sparverius ; Bossu et al., 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Of the 26 candidate genes tested for signals of positive selection, two showed significance: BCO1 (p = 0.037) and KCTD21 (p = 0.032; Table 2). These genes are associated with plumage color and dispersal, respectively (Ruegg et al, 2014; Toews, Hofmeister & Taylor, 2017; San-Jose et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Potassium channel tetramerization domain, KCTD21 , is associated with dispersal, migration, and the circadian clock (San-Jose et al, 2023). Dispersal and migration are two separate, but possibly intertwined, processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative lag in genomic research on aquatic species, coupled with the heterogeneity and high complexity of their genomes, has limited the application of high-throughput sequencing techniques. However, recent advancements in RAD-seq have introduced novel tools for studying aquatic species [20][21][22]. This technology has gained widespread popularity in breeding programs because of its many advantages, such as consistent size of digested DNA fragments, streamlined library construction procedures, and high accuracy.…”
Section: Introductionmentioning
confidence: 99%